Can you please explain this step v = a*(c/(c+b)). I am not able to understand as how you arrived on this step from the previous one:
If I have to divide a in the ratio b : c then it will be a * b/(b+c) and a * c/(b+c) by standard ratio logic…
(For example if I have to divide 40 in the ratio 3 : 5 I will do 40 * 3 / 8 and 40 * 5 / 8, right?)
I did not understand how (w*c/b) became (a*c/(c+b))
a = v+w and inverted componendo should do the trick 🙂
didn’t get the last comment of yous. Can you please elucidate ? 🙂
v/w = c/b
Now use inverted componendo [ 2/3 = 4/6 –> 2/(2+3) = 4/(4+6) right?.. similar ]
v/(v+w) = c/(c+b)
But from the figure, v+w=a
So, v/a = c/(c+b)
v= a. c/(c+b) 🙂
For the first question, a slightly simpler way would be to consider Triangle AOB.
Angle ABO = 45 ( Since angle bisected there) We can directly get Angle BAO 🙂
True 🙂 Nice spot!
Fill in your details below or click an icon to log in:
You are commenting using your WordPress.com account. ( Log Out / Change )
You are commenting using your Twitter account. ( Log Out / Change )
You are commenting using your Facebook account. ( Log Out / Change )
You are commenting using your Google+ account. ( Log Out / Change )
Connecting to %s
Notify me of new comments via email.